Shari’ah-Compliant E-Commerce Models and Consumer Trust - Muhammad Kholifatul I Ardiansyah; Yunizar Yunizar; Budi Harsanto (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This study is aimed at finding out the real picture of Shari’ah-compliant E-commerce model and consumer trust in e-commerce today, analyzing its drawbacks, and finding out how they influence each other. Shari'ah-compliant E-commerce model is a model that describes how e-commerce should run in accordance with the provisions of the Shari’ah. Broadly speaking, e-commerce in the perspective of Shari’ah must comply with some rules, namely: 1. the form of the offer and transaction agreement; 2. the transacting parties (buyers and sellers); 3. Objects and prices in the transaction; 4. Free from major prohibitions in transactions. The sample in this study is Indonesian citizen who are consumers of e-commerce. This research uses descriptive and statistical methods with multiple linear regression model. This model is considered relevant and good to be studied in order to enlighten how e-commerce is currently in the perspective of IslamDOI: 10.15408/aiq.v8i2.2913